2018
DOI: 10.1007/978-3-030-00847-5_21
|View full text |Cite
|
Sign up to set email alerts
|

A Volunteer Design Methodology of Data Warehouses

Abstract: In the context of Volunteered Geographic Information (VGI), volunteers are not involved in the decisional processes. Moreover, VGI systems do not offer advanced historical analysis tools. Therefore, in this work, we propose to use Data Warehouse (DW) and OLAP systems to analyze VGI data, and we define a new DW design methodology that allows involving volunteers in the definition of analysis needs over VGI data. We validate it using a real biodiversity case study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…To the best of our knowledge, only [7] investigates the collaborative design of cube schemata in crowdsourcing scenarios taking the profile of volunteers into account. In particular, the authors propose a DW design methodology where three groups of users have been identified: volunteers, committers, and BI experts.…”
Section: Multidimensional Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, only [7] investigates the collaborative design of cube schemata in crowdsourcing scenarios taking the profile of volunteers into account. In particular, the authors propose a DW design methodology where three groups of users have been identified: volunteers, committers, and BI experts.…”
Section: Multidimensional Modelingmentioning
confidence: 99%
“…So far, not much has been said in the literature about this. In an attempt to fill this gap, the authors of [7] investigated the collaborative design of cube schemata, proposing a methodology that relies on three groups of users: volunteers (nonauthoritative users who express some preliminary analysis needs), committers (authoritative users who collaboratively validate the volunteers proposals), and DW experts (who take care of all technical issues related to the development of the DW). Volunteers can give their feedback about the cube schemata; to achieve a consensus about the elements of these schemata, they use a Group Decision Support System (GDSS), i.e., a software tool that allows the management of group meetings with mathematical methods for finding solutions to problems that are unstructured in nature [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of DW design, this corresponds to the fusion of a set of multidimensional schemata, for which some approaches have been proposed in the literature. We adopt the one proposed in [47], which produces the schema shown in Fig. 15 starting from the ones in Figs.…”
Section: Multidimensional Modelingmentioning
confidence: 99%